Winter temperatures decrease swimming performance and limit distributions of tropical damselfishes. (18th September 2015) - Johansen, Jacob L.; Steffensen, John F.; Jones, Geoffrey P.
Abstract : Planktivorous coral reef fishes occupy sheltered to exposed reef habitats based on their ability to swim and foraging within the current. However, climate driven fluctuations in temperature can reduce this ability to swim and direct the distribution of species to more sheltered habitats. Abstract : Coral reefs within 10° of the equator generally experience ≤3°C seasonal variation in water temperature. Ectotherms that have evolved in these conditions are therefore expected to exhibit narrow thermal optima and be very sensitive to the greater thermal variability (>6°C) experienced at higher latitudes (≥10°N/S). The impact of increased thermal variability on the fitness and distribution of thermally sensitive reef ectotherms is currently unknown. Here, we examine site-attached planktivorous coral reef damselfishes that rely on their physiological capacity to swim and forage in the water column year round. We focus on 10 species spanning four evolutionarily distinct genera from a region of the Great Barrier Reef that experiences ≥6°C difference between seasons. Four ecologically important indicators showed reduced performance during the winter low (23°C) compared with the summer peak (29°C), with effect sizes varying among species and genera, as follows: (i) the energy available for activity (aerobic scope) was reduced by 35–45% in five species and three genera; (ii) the energetically most efficient swimming speed was reduced by 17% across all species; and (iii) the maximal critical swimming speed and (iv) the gait transition speed (the swimming mode predominantly used for foraging) were reduced by 16–42% in six species spanning all four genera. Comparisons with field surveys within and across latitudes showed that species-specific distributions were strongly correlated with these performance indicators. Species occupy habitats where they can swim faster than prevailing habitat currents year round, and >95% of individuals were observed only in habitats where the gait transition speed can be maintained at or above habitat currents. Thermal fluctuation at higher latitudes appears to reduce performance as well as the possible distribution of species and genera within and among coral reef habitats. Ultimately, thermal variability across latitudes may progressively cause sublethal changes to species performance and lead to a contraction of biogeographical range.